2018
DOI: 10.1016/j.envpol.2018.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Sub-inhibitory concentrations of heavy metals facilitate the horizontal transfer of plasmid-mediated antibiotic resistance genes in water environment

Abstract: Although widespread antibiotic resistance has been mostly attributed to the selective pressure generated by overuse and misuse of antibiotics, recent growing evidence suggests that chemicals other than antibiotics, such as certain metals, can also select and stimulate antibiotic resistance via both co-resistance and cross-resistance mechanisms. For instance, tetL, merE, and oprD genes are resistant to both antibiotics and metals. However, the potential de novo resistance induced by heavy metals at environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
133
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(172 citation statements)
references
References 47 publications
5
133
4
Order By: Relevance
“…A previous study has shown that the two plasmids included in this study are inter-and intra-species transferable at different conditions, indicating that they may contribute to the maintenance of antibiotic-resistant genes in the environment. 29 In contrast to earlier studies, which show that Zn and Cu are associated with increased conjugation, [50][51][52][53] we found that Zn and Cu reduced the conjugation frequency between E. coli strains in a concentrationdependent manner. There was also no difference in the number of colonies on the donor-and recipient-selective plates from the mating cultures, which confirms that Zn and Cu does not affect growth of donor-or recipient strains.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A previous study has shown that the two plasmids included in this study are inter-and intra-species transferable at different conditions, indicating that they may contribute to the maintenance of antibiotic-resistant genes in the environment. 29 In contrast to earlier studies, which show that Zn and Cu are associated with increased conjugation, [50][51][52][53] we found that Zn and Cu reduced the conjugation frequency between E. coli strains in a concentrationdependent manner. There was also no difference in the number of colonies on the donor-and recipient-selective plates from the mating cultures, which confirms that Zn and Cu does not affect growth of donor-or recipient strains.…”
Section: Discussioncontrasting
confidence: 99%
“…59 To understand the effect of Zn and Cu on conjugation in our study, we performed a real-time transcriptional analysis that showed a reduction in expression of conjugation-associated genes in response to subinhibitory concentrations of Zn and Cu. However, our findings contrast the report by Zhang et al, 52 who found that different concentrations of heavy metals increased conjugation and upregulated the expression of genes involved in conjugation of plasmids. Strain background, concentrations of the metals, and experimental conditions might explain the contradictory results.…”
Section: Discussioncontrasting
confidence: 99%
“…Heavy metals persist within sediment, where they increase the half-life of antibiotics [66]. Even at low concentrations, heavy metals can contribute to the emergence and spread of antimicrobial-resistant strains through coselection of genetic elements encoding both heavy metal and antibiotic resistance genes [67][68][69][70][71]. This was recently confirmed by the selection of antibiotic-resistant enterococci by very low heavy-metal concentrations [72].…”
Section: Selection Of Drug-resistant Microorganism Can Occur In Surfamentioning
confidence: 94%
“…For instance, heavy metal ions (e.g., Cu 2+ , Cd 2+ , Hg 2+ and Zn 2+ ) and nanoparticles (e.g., ZnO NPs, Al 2 O 3 NPs and Ag NPs) have been reported to induce antibiotic resistance via co-selection or direct mutation [12,13,15,16]. In addition, heavy metal ions (including Cu 2+ , Ag + , Cr 6+ , Ti 4+ and Zn 2+ ) [17][18][19] and nanoparticles (e.g., Al 2 O 3 NPs, CuO NPs, Ag NPs and TiO 2 NPs) [18][19][20][21] could promote the transfer of ARGs via conjugation. However, it is unclear whether heavy metal-based NPs and ions could enhance the dissemination of ARGs via natural transformation.…”
Section: Introductionmentioning
confidence: 99%